Peningkatan Keefektifan Pengembangan SDM Dengan Pendekatan Development Needs Analysis (DNA) Di Perusahaan “X” - Helmi F Wandara; Mansur Benyamin Latuconsina; Sri Sundari; Marisi Pakpahan (Jurnal Cakrawala Akademika, 2024)
This research aims to analyze the effectiveness of Human Resources (HR) development using the Developmental Needs Analysis (DNA) approach at Company X. Through analysis of individual, team and organizational development needs, this research identifies competency gaps, specific training and development needs, designing relevant programs, and measuring their impact on employee performance. The research method used is qualitative with data collection through in-depth interviews and document analysis. The research results show that applying the DNA approach can increase the relevance of HR development programs to organizational and individual needs, employee performance, job satisfaction and organizational effectiveness. However, there are still several obstacles that need to be overcome to achieve optimal results. This research contributes to the development of HR development theory and practice, especially in the context of companies in Indonesia, and provides suggestions for Company X to continue to improve and develop a DNA-based HR development system.